Attenuation of Electromagnetic Interference Generated by High-Frequency Switching Devices - Chaiyan Jettanasen; Atthapol Ngaopitakkul; Chaichan Pothisarn (My University, 2022)
A frequency modulation (FM) radio signal receiver is an important device for radio transmitters. The FM radio signal receiver is mounted on the radio transmitter, and its circuit is connected to the electronic system inside the radio transmitter. Therefore, it is necessary to consider the electromagnetic interference (EMI) produced by the FM radio signal receiver to prevent damage caused by interference. This study investigated the EMI characteristics of an FM radio signal receiver in terms of conducted emissions and radiated emissions. The conducted emissions were measured in the frequency range of 150 kHz to 30 MHz and exceeded the CISPR22 standard at frequencies of 370 kHz (−2.4 dB) and 480 kHz (−6.5 dB). The radiated emissions were measured in the frequency range of 30 MHz to 1000 MHz and exceeded the EN55022 standard at a frequency of 33.93 MHz (−13 dB). The conducted emissions were reduced using an axial ferrite bead, while the radiated emissions were attenuated using multipoint grounding and shielding techniques. The axial ferrite beads could attenuate the conducted emissions by 8 dB. The multi-point grounding and shielding techniques attenuated the radiated emissions by approximately 22 dB. These EMI attenuation methods demonstrated satisfactory attenuation performance and resulted in the EMI satisfying the relevant standards.
Keywords: Electromagnetic Compatibility and Noise Suppression; Electromagnetic Compatibility and Measurements; Advanced Antenna and Metasurface Technologies